Physical exercise for the prevention and treatment of type 2 diabetes - Sanz, C.; Gautier, J.-F.; Hanaire, H. (Diabetes & metabolism, 2010)
The prevalence of type 2 diabetes is rapidly increasing worldwide, yet its primary prevention and treatment are still a challenge. The objectives of this review are to assess the effects of exercise on the prevention of type 2 diabetes in high-risk individuals and on glycaemic control in type 2 diabetic patients. Considering the available reports, there is unequivocal and strong evidence that physical exercise can prevent or delay progression to type 2 diabetes in subjects with impaired glucose tolerance. Also, lifestyle interventions, including diet and physical exercise, can result in a reduction of around 50% in diabetes incidence that persists even after the individual lifestyle counselling has stopped. In addition, short-term randomized studies have confirmed that physical training based on endurance and/or resistance exercises can also improve blood glucose control in type 2 diabetics with a mean glycated haemoglobin decrease of 0.6%. Thus, physical exercise should be part of any therapeutic strategy to slow the development of type 2 diabetes in high-risk individuals and to improve glucose control in type 2 diabetes. La prévalence du diabète ne cesse d’augmenter dans le monde. La prévention et le traitement de cette maladie demeurent un défi. Les objectifs de cette revue sont d’évaluer les effets de la pratique d’une activité physique, d’une part, sur l’incidence du diabète chez des sujets à risque (intolérants au glucose) et, d’autre part, sur l’équilibre glycémique des diabétiques de type 2. Au vu des données disponibles, il existe des arguments forts pour dire que l’activité physique prévient ou retarde l’apparition du diabète. Les modifications du mode de vie incluant l’alimentation et l’activité physique permettent une réduction de 50 % de l’incidence du diabète et cet effet persiste même après l’arrêt de l’intervention. L’exercice physique améliore l’équilibre glycémique des sujets diabétiques de type 2 avec une réduction de l’HbA 1c de 0,6 % en moyenne. Les activités d’endurance et de résistance doivent être toutes deux encouragées chez les sujets diabétiques de type 2.